ANALISIS FAKTOR PENENTU KINERJA PEMERINTAH KELURAHAN (Suatu Studi Di Kecamatan Mapanget Kota Manado) - Pesoth, Willy (JURNAL ADMINISTRASI BISNIS, 2014)
ABSTRACT : The performance of the government apparatus is a crucial issue often faced by local governments, especially at village level. The low performance of the government apparatus at the Village district of Manado Mapanget not be separated from some of the determining factors, such as the factor of education / skills, compensation, coordination, mentality and work discipline in running the administrative tools duties of government. This study aimed to find out there are at least influence the factors of education / skills, compensation, coordination, mental attitudes and work discipline on the performance of district governments in Sub Mapanget. Based on the results of data analysis found that the average determinants, such as formal education, skills or formal education, kompensai, coordination, mental attitude and discipline administrative tool, is also still low Uncategorized. Thus, all proved decisive factor affecting the device performance Mapanget village in the District is still in the low category. This situation clearly affects the performance of the device itself, which village was still significantly lower Uncategorized. The results concluded that the factors of skill, compensation, coordination, mental attitude and discipline administrative tool, although still low but associated Uncategorized contributive and significant or very significant to the performance of administrative devices, especially in Sub Mapanget. This gives the meaning that if all the determinants is sought to be improved, it will encourage the improvement of administrative performance of the device itself. Keywords: determinant factors, performance of administrative tools